Fabrication of Cu-Zn Alloy Micropillars by Potentiostatic Localized Electrochemical Deposition. Issue 8 (3rd May 2019) - Wang, Chun-Yao; Lin, Jing-Chie; Chang, Yung-Chieh; Tseng, Yao-Tien; Ciou, Yong-Jie; Hwang, Yean-Ren
Abstract : Cu-Zn alloy micropillars were fabricated by a potentiostatic localized electrochemical deposition (LECD) process. This process was carried out via micro-anode-guided electroplating in a pyrophosphate bath at a constant negative potential in the range −1.85 to −2.05 V. Different products were produced, depending on the initial inter-electrode gap employed. Thus, at an initial gap of 40 μm, the process afforded micropillars with a single α-brass crystal phase and at.% Zn contents in the range 17.20–32.01%. A reduction in the initial gap to 30 μm resulted in varied micropillar crystal phases (α, β, and β + β') with at.% Zn contents in the range 37.12–68.94. The simulation commercial software COMSOL 5.2 was employed to correlate the asymmetric distribution of the electric field to the experimental parameters and pillar characteristics. The resultant data was then used to delineate the dependence of the field strength on the crystal phase, composition, growth rate, and micropillar diameters. Finally, a potentiodynamic cathodic polarization study was employed to elucidate the mechanism for the fabrication of the Cu-Zn alloy micropillars via potentiostatic LECD.